Availability of information and representation effects in the centipede game - Paolo Crosetto; Marco Mantovani (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The paper presents the results of a novel experiment testing the effects of environment complexity on strategic behavior, using a centipede game. Behavior in the centipede game has been explained either by appealing to failures of backward induction or by calling for preferences that induce equilibria consistent with observed behavior. By manipulating the way in which information is provided to subjects we show that reduced availability of information is sufficient to shift the distribution of take-nodes further from the equilibrium prediction. On the other hand, similar results are obtained in a treatment where reduced availability of information is combined with an attempt to elicit preferences for reciprocity, through the presentation of the centipede as a repeated trust game. Our results could be interpreted as cognitive limitations being more effective than preferences in determining (shifts in) behavior in our experimental centipede. Furthermore our results are at odds with the recent ones in Cox and James (2012), suggesting caution in generalizing their results. Reducing the availability of information may hamper backward induction or induce myopic behavior, depending on the strategic environment.
Keywords: C72; C73; C91; 330; Centipede; Backward Induction; Representation effects; Extensives Spiel; Wiederholte Spiele; Vertrauen; Unvollkommene Information; Test